OsPAL2-1 Mediates Allelopathic Interactions Between Rice and Specific Microorganisms in the Rhizosphere Ecosystem - Li, Yingzhe; Jian, Xin; Li, Yue; Zeng, Xiaomei; Xu, Lining; Khan, Muhammad Umar; Lin, Wenxiong (Frontiers in Microbiology, 2020)
The use of plant allelopathy to control weeds in the field has been generally recognized as a win-win strategy because it is an environmentally friendly and resource-saving method. The mechanism of this natural weed-control method relies on allelochemicals, the rhizosphere microbiome, and their bio-interaction, and exploring the link between allelochemicals and specific microbes helps accelerate the application of allelopathic characteristics in farming. In this study, we used allelopathic rice PI312777 (PI), its genetically modified OsPAL2-1 repression (PR) or overexpression (PO) lines, and non-allelopathic rice Lemont (Le) as donor plants to reveal the bio-interaction between rice allelochemicals and rhizosphere specific microorganisms. The results showed a higher content of phenolic acid exudation from the roots of PI than those of Le, which resulted in significantly increased the population of myxococcus in the rhizosphere soil. Transgenic PO lines exhibited increasing exudation of phenolic acid, which led to the population of Myxococcus xanthus in the rhizosphere soil of PO was significantly increased, while PR showed the opposite result in comparison with the wild type of PI. Exogenous application of phenolic acid induced the growth of M. xanthus, and the expressions of chemotaxis-related genes were up-regulated in M. xanthus. In addition, quercetin was identified in the culture medium; according to the bioassay determination, a quercetin concentration of 0.53 mM inhibited the root length by 60.59%. Our study indicates that OsPAL2-1 is among the efficient genes that regulate rice allelopathy by controlling the synthesis of phenolic acid allelochemicals, and phenolic acid (ferulic acid, FA) induces the chemotactic aggregation of M. xanthus, which promoted the proliferation and aggregation of this microbe. The potential allelochemical, quercetin was generated from the FA-induced M. xanthus cultured medium.